Spoken Language Interface for Mobile Devices - Freitas, J.; Freitas, J.; Lopes, A.; Maria João Barros; Dias, J. (Human Language Technology. Challenges of the Information Society, 2009)
In this paper, we present a set of optimizations for a spoken language interface for mobile devices that can improve recognition accuracy and user interaction experience. A comparison between a speech and a graphical interface, when used to accomplish the same task, is provided. The implications of developing a spoken language interface and integrating speech recognition and text-to-speech modules for European Portuguese in a mobile device are also discussed. The paper focuses on the speech recognition module and an algorithm for name-matching optimization that gives the user a more comfortable interaction with the device. Usability evaluation trials have shown that spoken language interfaces can provide an easier and more efficient device use, especially within a community of users less experienced in handling mobile devices.